An Analysis of The Application of Sharia Business Ethics Among Vendors at Tourist Markets (A Case Study of Lereng Market in Bukittinggi) - Pitri Sesnawati; Iiz Izmuddin (International Journal of Education, Information Technology, and Others, 2026)
This study aims to analyze how the implementation of sharia business ethics by traders in Lereng Market, and to identify the factors that cause high prices of goods sold by traders to consumers. The research method used is descriptive qualitative with data collection methods through interviews, direct observation, and documentation. The informants of this study consisted of traders, consumers and market managers. The results of this study indicate that some traders have implemented the values of sharia business ethics, such as honesty in conveying the condition of goods and responsibility in setting prices. However, it is undeniable that there are still traders who have not implemented sharia business ethics in their trading activities on the grounds of wanting to get higher profits. In practice, deviations are still found such as the sale of goods at high prices and injustice in service.